2014
DOI: 10.1088/1748-3182/9/3/036017
|View full text |Cite
|
Sign up to set email alerts
|

Movable shark scales act as a passive dynamic micro-roughness to control flow separation

Abstract: Shark scales on fast-swimming sharks have been shown to be movable to angles in excess of 50°, and we hypothesize that this characteristic gives this shark skin a preferred flow direction. During the onset of separation, flow reversal is initiated close to the surface. However, the movable scales would be actuated by the reversed flow thereby causing a greater resistance to any further flow reversal and this mechanism would disrupt the process leading to eventual flow separation. Here we report for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Also unknown is the extent to which denticles move on their bases during locomotion and change angle relative to the skin. Motta et al () have suggested that, for shortfin mako sharks, denticles can be erected passively and that this may be used to control boundary layer profiles by inhibiting backflow (Lang et al, ). Wen et al () presented experimental data supporting an alternative hypothesis that having slightly mobile denticles would reduce the cost of locomotion by minimizing the skin bending force that results from denticle crowns pressing on each other as the body oscillates and produces skin curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Also unknown is the extent to which denticles move on their bases during locomotion and change angle relative to the skin. Motta et al () have suggested that, for shortfin mako sharks, denticles can be erected passively and that this may be used to control boundary layer profiles by inhibiting backflow (Lang et al, ). Wen et al () presented experimental data supporting an alternative hypothesis that having slightly mobile denticles would reduce the cost of locomotion by minimizing the skin bending force that results from denticle crowns pressing on each other as the body oscillates and produces skin curvature.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, considerable progress has been made in the design and manufacture of nanomaterials, nanodevices, functional surfaces, etc. by mimicking biology and nature ( Bhushan, 2009 ; Dean and Bhushan, 2012 ; Lang et al, 2014 ). A fine example of bionic design is the biomimetic drag reduction that is achieved using a special microstructure surface which emulates the non-smooth surface of certain natural organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have demonstrated that shark scales are flexibly connected to the underlying skin and thus are capable of bristling [8] and that preventing scales from bristling increases backflow in a turbulent, reversing flow [43,44], but this study provides the first direct documentation of passive bristling by shark scales in reversing flows. If scale bristling functions in drag reduction of these high Re swimmers, there would be strong selective pressure for this mechanism to function at cruising speeds.…”
Section: Discussionmentioning
confidence: 72%